2008
DOI: 10.3357/asem.2315.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle of UK Commercial Aircrews Relative to Air Traffic Controllers and the General Population

Abstract: The differences between aircrews and the general population are consistent with a strong "healthy worker effect." Aircrews and ATCOs undergo a similar employment selection process and thus taking the latter as the reference population, in addition to the general population, will help to minimize the "healthy worker effect" and gain insight into its biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
2
18
1
Order By: Relevance
“…However, such comparison may hide increases in specific site-specific cancer risks experienced by this occupational group. To be able to identify such increases, if present, we took UK ATCOs, which have a similar socioeconomic background and type of medical surveillance as flight crew, 13 as a comparison group. We found that flight crew had similar cancer risks to ATCOs, arguing against their risks being driven mainly by occupation-specific exposures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such comparison may hide increases in specific site-specific cancer risks experienced by this occupational group. To be able to identify such increases, if present, we took UK ATCOs, which have a similar socioeconomic background and type of medical surveillance as flight crew, 13 as a comparison group. We found that flight crew had similar cancer risks to ATCOs, arguing against their risks being driven mainly by occupation-specific exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and data sources have been described in detail elsewhere. [13][14][15] In summary, the study population was identified from the Medical Records System (MRS) of the UK Civil Aviation Authority (CAA), which holds data gathered from routine surveillance examinations of holders of UK licences, that is, holders of a UK professional flight crew licence or ATCO licence. Flight crew licences comprise licenses for airline transport pilot (ATPL), senior commercial pilot, commercial pilot, basic commercial pilot, flight engineer and flight navigator.…”
Section: Methodsmentioning
confidence: 99%
“…An unexposed control population with otherwise similar lifestyle was not recruited at the inception of the cohort. Newer studies suggest that air traffic controllers might be a suitable comparison group [28,31]. Furthermore, the computed occupational doses do not take into account work periods at airlines other than the two airlines used to compile the cohort, and may thus have been underestimated.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…There is probably a low prevalence of smoking in this cohort since they had a low lung cancer incidence (24,25); a low smoking prevalence was found in other flying cohorts (32,33). This tends to reduce the AMI incidence.…”
Section: Linnersjö Et Almentioning
confidence: 99%